Rheology of methane hydrate slurries formed from water-in-oil emulsion with different surfactants concentrations. (1st September 2020) - Liu, Zaixing; Song, Yongchen; Liu, Weiguo; Liu, Ran; Lang, Chen; Li, Yanghui
Abstract: As oil and gas production moves into ultra-deep water, hydrate blockage has been a major flow assurance issue. Transport in the form of flowing hydrate slurry is an effective method to prevent hydrate blockage with an addition of surfactants. To determine the impact of surfactants on rheological behavior of hydrate slurry, the high-pressure rheological experiment was conducted on methane hydrate slurry formed from emulsion with 50 vol% water cut but different surfactants concentrations. The emulsions were prepared with deionized water, n-decane and two non-ionic surfactants (Span 80 as an anti-agglomerant and Tween 80 as a co-surfactant). The experimental results indicate that a lower surfactants concentration would greatly accelerate hydrate formation, causing blockage in a shorter time. While the higher the surfactants concentration, the more stable the slurry when hydrate formation. As the surfactant concentration was over 5 wt% in the oil phase, slurry viscosity decreased significantly, and hydrate slurry showed a good flow performance. Furthermore, a simulation of shut-in and restart was conducted after slurry reaching a steady-state. It was found that during the first 10 min of shut-in process, yield stress at restart was basically unchanged, while when the shut-in time exceeded 20 min, the yield stress increased significantly with the increase of the shut-in time, and an increase of surfactants concentration would have a negative effect on this trend. As the surfactant concentration was over 5 wt%, the flow performance of hydrate slurry remained good after 1280 min shut-in and restart, with little change in rheological behavior.